(3GdLfi GdOGfj aj MQha GdeYGfjs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s ((3YHOGdbGOQ Hf eMeO Hf eMeO GdWhNj GdTGaYj s)
(3ChdgG (B:s
(3hHYO, aEfg deG cGfJ ebGUO cdGe GdYQH Ydi GNJdGa Ufhag eHfjkG CcKQgG Ydi eYGfj MQhag s
(3BNQgG (B:s
(3hEfeG CgedJ PcQgG gfGc dTgQJgG hZQGHI Gdbhd HMQajJgG hGdcdGe YdjgG ehVY gh Cdjb Hg ef gPG GdcJGH, hGddg Gdehab, ced cJGH s
(3fSNI NGeSI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3hHgG fXGe GdJYbjHIs
(3cJHJ ef fSNI ajgG CfgG cJHJ ef fSNI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs